Manfaat Musik pada Penanganan Demensia - Halimsetiono, Elita (JURNAL KESEHATAN PRIMER, 2025)
Introduction: People with dementia can experience depression, anxiety, and agitation due to memory loss. This can also lead to loss of independence and isolation from family and friends. Music has been proven to be an effective non-pharmacological treatment option in reducing depression, anxiety, and agitation caused by dementia. This article provides an overview of the benefits of music in treating dementia. Methods:  This article is a literature review with the keywords "cognitive function," "dementia," "music," and "psycho-behavioral," which were searched through the Google Scholar database. Inclusion criteria include scientific works originating from international journals in the period 2016-2025, which can be accessed online in full-text form. Results: The search for articles discussed in this research was 6 international journals. Music can reduce depression, anxiety, and agitation caused by dementia. In addition, music has benefits for both people with dementia and their caregivers. Conclusion: Music is a non-pharmacological therapy that is beneficial for dementia patients and their caregivers. It also helps improve thinking and behavior in people with dementia. Music can be considered as another option for treating dementia, but these benefits still require further research.